(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Global warming and climate change are predicted to have a major impact on rice production, necessitating both adaption and mitigation strategies. Among the agricultural crops, rice is highly vulnerable to climatic extremes such as drought, unseasonal rains, flooding, and high temperature stress. However, there is a dearth of short duration varieties which will fit well into the reduced growing period brought about by the changing climatic and rainfall pattern. With this point of view, a study was conducted at the research field of Bangladesh Agricultural Development Corporation (BADC) situated at Subarnachar sub-district under Noakhali district of Chittagong division in Bangladesh during July-November 2018 to sort out some cultivars for their earliness, adaptability, yield and other agronomic traits. Total 11 Kanihati cultivars viz., Kanihati 1, Kanihati 2, Kanihati 3, Kanihati 4, Kanihati 6, Kanihati 7, Kanihati 8, Kanihati 9, Kanihati 10, Kanihati 11 and Kanihati 12 were tested against the standard check BRRI dhan52. Test materials were arranged in a randomized complete block design with three replications in three blocks. Result reveals that Kanihati 9, Kanihati 7, and Kanihati 3 were qualified for further screening and evaluation processes for few more years as they were 20 days earlier having the yield potentials of statistically similar with BRRI dhan52 Res. Agric., Livest. Fish.7(3): 393-402, December 2020